Graduate profile of guidance and counseling department faculty of education universitas negeri semarang - Nusantoro, Eko; Kurniawan, Kusnarto; Suharso, Suharso (COUNS-EDU: The International Journal of Counseling and Education, 2017)
Faculty of Education Universitas Negeri Semarang, and 3) readiness alumni of Guidance and Counseling Department Education of Faculty Universitas Negeri Semarang  to compete in the  work world. The method used is a survey-descriptive. The population for this study is the alumni of Guidance and Counseling Department Faculty of Education Universitas Negeri Semarang that graduated in 2013, 2014, 2015, and 2016 in the region of Central Java Province. The sampling used cluster random sampling techniques (cluster random sampling area). Cluster sampling technique procedures implemented by selecting a sample in Central Java Province randomly. An instrument which is used was questionnaire and interview. Quantitative data analysis techniques using descriptive statistical data and  qualitative data analysis using interviews. The results showed that 1) the competence of alumni Guidance and Counseling Department  Faculty of Education Universitas Negeri Semarang very well in accordance with the Regulation of the Minister of Education and Culture of the Indonesia Republic No. 27 of 2008 on Standards Academic Qualifications and Competencies Counselors Indonesia, 2) the suitability of the field work with the field of graduate studies Study Guidance and Counseling Department  Faculty of Education Universitas Negeri Semarang is very appropriate, and 3) the alumni are very ready to compete with the alumni Guidance and Counseling Department from other universities.